The Immunoregulatory Activity of Mesenchymal Stem Cells: ‘State of Art’ and ‘Future Avenues’ - Fierabracci, Alessandra; Fattore, Andrea Del; Muraca, Maurizio (Current Medicinal Chemistry, 2016)
Mesenchymal stem cells are spindle-like plastic adherent multipotent cells that can differentiate into multiple specialized cell types including osteoblasts, chondrocytes and adipocytes. They were isolated from many tissues and organs and they contribute to the maintenance and regeneration of several tissues. Besides their ability of self-renewal, they have recently been shown to have a clinical/therapeutic potential particularly for their immunomodulatory properties. Indeed recent studies suggested a potential application of MSCs for the treatment of experimental autoimmune disorders. It was demonstrated that their effects are in part mediated by the release of soluble factors or extracellular vesicles, including exosomes and microvesicles, stimulating or inhibiting target cells. This review will describe the secretome of MSCs, pointing the attention on the components relevant for their immunodulatory activities.
Keywords: Secretome